Heparin-binding EGF-like growth factor: mechanisms of biological activity and potential therapeutic applications - L. M. Dronko; T. M. Lutsenko; N. V. Korotkevych; I. O. Vovk; D. A. Zhukova; S. I. Romaniuk; A. A. Siromolot; A. J. Labyntsev; D. V. Kolybo (The Ukrainian Biochemical Journal)
The diphtheria toxin receptor on sensitive mammalian cells is known as the membrane anchored precursor of heparin-binding EGF-like growth factor (HB-EGF). When the precursor is cleaved by metalloproteinases, a soluble form (sHB-EGF) is formed that can bind to the EGF receptors, resulting in activation of signaling pathways that regulate cell proliferation, differentiation, migration, and inhibition of apoptosis. The ability of HB-EGF to cause both positive and negative consequences for organism underscores the complexity of its biological functions and the need for a nuanced understanding of its role in health and disease. In this review the data on the HB-EGF structure, biological activity, involvement in the mechanism of diphtheria toxin action, wound healing, tumor progression as well as the methods of HB-EGF delivery are summarized.